Interprofessional Team-Based Learning: A Qualitative Study on the Experiences of Nursing and Physiotherapy Students - Ho, Jacqueline Mei-Chi; Wong, Arnold Yu-Lok; Schoeb, Veronika; Chan, Alex Siu-Wing; Tang, Patrick Ming-Kuen; Wong, Frances Kam-Yuet (Frontiers in Public Health, 2022)
Traditional discipline-specific training has limitations in facilitating inter-professional communication and collaboration. To address this issue, two local universities in Hong Kong launched an interprofessional team-based learning program to allow the undergraduate healthcare students to form teams and experience collaborative problem-solving. This study aimed to evaluate the experiences of nursing and physiotherapy undergraduates following interprofessional learning activities. Twenty-seven 3rd-year nursing and physiotherapy undergraduates were recruited through purposive sampling. Semi-structured interviews were conducted, and written feedback was solicited until data saturation was achieved. An inductive thematic analysis was used for the data, and each theme was mutually exclusive. The findings revealed the positive experiences of the students with this interprofessional learning activity. Three main themes emerged: (1) the process of interprofessional learning; (2) profession-related outcomes of interprofessional learning; and (3) patient-related outcomes of interprofessional learning. The study indicated that interprofessional team-based learning activities enhanced learning experiences of the students through interactive learning with other healthcare students. Experiences of relationships that are trustful and complementary allow students to develop confidence in knowledge transfer and in interprofessional collaboration, as well as in providing a holistic patient-centered care. These findings substantiate the importance and value of interprofessional learning in healthcare education.